2022
DOI: 10.1002/jdn.10206
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in cognitive behavioral alterations and barrel cortex neuronal responses in rats exposed prenatally to valproic acid under continuous environmental enrichment

Abstract: Autism spectrum disorder is a developmental disorder that can affect social interactions and sensory-motor behaviors. The present study investigates the effect of environmental enrichment (EE) on behavioral alterations and neuron responses associated with the barrel cortex of young adult female and male rats exposed prenatally to valproic acid (VPA). Pregnant female rats were pretreated with either saline or VPA (500 mg/kg, IP) on day 12.5 of gestation. Male and female pups were exposed to either EE or standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
3
4
0
Order By: Relevance
“…The present study showed in the three‐chamber social interaction test, prenatal treatment with valproic acid significantly reduced the percentage of preference index to Strangers 1 and 2 during sociability and novel social phases in both sexes of the Val groups compared with the CTL groups. It has been shown that prenatal injection of valproic acid reduces the sociability and novelty indices (Hara et al., 2017; Sabzalizadeh et al., 2022; Schiavi et al., 2019), which were in‐line with our study. It has been noted that the decrease in PIST2 in this test is an important criterion for induction of the ASD in rodents (Nygaard et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study showed in the three‐chamber social interaction test, prenatal treatment with valproic acid significantly reduced the percentage of preference index to Strangers 1 and 2 during sociability and novel social phases in both sexes of the Val groups compared with the CTL groups. It has been shown that prenatal injection of valproic acid reduces the sociability and novelty indices (Hara et al., 2017; Sabzalizadeh et al., 2022; Schiavi et al., 2019), which were in‐line with our study. It has been noted that the decrease in PIST2 in this test is an important criterion for induction of the ASD in rodents (Nygaard et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Unlike the control groups (CTL-TS vs. CTL), TS caused an increase in the body weight gain of the Val-TS groups compared to the Val groups of both sexes (significant for females), which was in-line with the findings of previous experiments (Akatsu et al, 2015;Caldji et al, 2000;Meerlo et al, 1999;Seiffe et al, 2022). The same result was obtained in the male-Val-TS-WD rats under both TS and WD conditionings com- proic acid reduces the sociability and novelty indices (Hara et al, 2017;Sabzalizadeh et al, 2022;Schiavi et al, 2019), which were in-line with our study. It has been noted that the decrease in PIST2 in this test is an important criterion for induction of the ASD in rodents (Nygaard et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Animal studies have also reported social interaction deficits (Sabzalizadeh et al , 2022; Taheri et al , 2022) and increased repetitive behaviors in VPA-exposed animals (Baronio et al , 2015; Eissa et al , 2018b). Our previous study showed social deficits in adult VPA-exposed rats (Taheri et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that genetic (De Rubeis et al , 2014; Hansen et al , 2015) and environmental (Chiarotti and Venerosi, 2020) factors influence the pathogenesis of ASD. Researchers have found that the maternal use of valproic acid (VPA) during pregnancy increases the risk of autism in humans (Ornoy, 2009) and rodents (Sabzalizadeh et al 2022; Haratizadeh et al 2023).…”
Section: Introductionmentioning
confidence: 99%